Diagnosis dan Tatalaksana Hipertensi Krisis - Samsu, Nur (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Hypertensive crises are divided into emergency and urgent hypertension. For most doctors, the differences between these two types of hypertensive crisis present their own challenges, especially in terms of therapy and follow-up. The main distinguishing feature of these two types of hypertensive crisis is the presence of ongoing acute target organ damage, not the degree of blood pressure (BP). A hypertensive emergency is a true medical emergency, which generally requires immediate lowering of BP, in an intensive care unit and short-term, easily titrated intravenous antihypertensive drug therapy. Common management strategies are based on hypertension-specific organ damage (HMOD); the onset of HMOD, especially time-sensitive ones such as acute ischemic stroke, acute ST-elevation myocardial infarction; and availability of facilities and resources. A hypertensive emergency is a state of severe or significant increase in BP but without acute damage to target organs. This type of hypertension does not require rapid lowering of BP, and can be treated on an outpatient basis with appropriate oral medications.